2012
DOI: 10.1002/jor.22293
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting‐produced porous titanium scaffolds regenerate bone in critical size cortical bone defects

Abstract: Porous titanium scaffolds have good mechanical properties that make them an interesting bone substitute material for large bone defects. These scaffolds can be produced with selective laser melting, which has the advantage of tailoring the structure's architecture. Reducing the strut size reduces the stiffness of the structure and may have a positive effect on bone formation. Two scaffolds with struts of 120-mm (titanium-120) or 230-mm (titanium-230) were studied in a load-bearing critical femoral bone defect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
156
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(165 citation statements)
references
References 28 publications
9
156
0
Order By: Relevance
“…The novel dithio-octonoate monomers exhibit high TBS to all metal adhesives tested after 2000 thermal cycles. These experimental results verified the excellent bondability of these new dithio -octonoate monomers to precious metals and alloys [30][31][32][33][34]. Comparison between dithio-octonoate monomers and sulfur-containing monomers in combination with precious metals and their alloys.…”
Section: Dithio-octonoate Monomers For Adhesion To Precious Metals Ansupporting
confidence: 69%
See 1 more Smart Citation
“…The novel dithio-octonoate monomers exhibit high TBS to all metal adhesives tested after 2000 thermal cycles. These experimental results verified the excellent bondability of these new dithio -octonoate monomers to precious metals and alloys [30][31][32][33][34]. Comparison between dithio-octonoate monomers and sulfur-containing monomers in combination with precious metals and their alloys.…”
Section: Dithio-octonoate Monomers For Adhesion To Precious Metals Ansupporting
confidence: 69%
“…Precious metals and their alloys used were Au, Pt, Pd, Ag alloy and Au -Ag -Pd alloy. After the primer pretreatment and bonding by MMA -PMMA / BPO -TBS resins, to precious metals and alloys after 2000 thermal cycles (31). In conjunction with Au, Ag alloy, and Au-Ag-Pd alloy, the three dithio-octonoate monomers (2-MEDT, 6-MHDT, 10-MDDT) exhibited significantly higher TBS than all conventional sulfurcontaining monomers .…”
Section: Dithio-octonoate Monomers For Adhesion To Precious Metals Anmentioning
confidence: 99%
“…In summary, an ideal scaffold for bone regeneration should facilitate cell attachment, infiltration and matrix deposition to guide bone formation [69] as well as providing initial mechanical support to the surrounding bone [70]. Porous titanium scaffolds can meet the mechanical strength and bone formation requirements without osseoinductive biomolecules [68]; however, the pore size of the scaffolds needs to be high for bone-ingrowth whereas, as the porosity increases, the mechanical strength and integrity of the structure decreases [71].…”
Section: Discussionmentioning
confidence: 99%
“…The bone marrowderived mesenchymal stromal cells of 8-week old male Sprague-Dawley rats (Charles River Laboratories, California, USA) were cultured in an osteogenic induction medium containing alpha-modified Eagle's medium (Invitrogen, California, USA) supplemented with 15% fetal bovine serum (Invitrogen), rials for bone engineering due to their high porosity, physical strength, biocompatibility, and osteoconductive properties (10,25,27). Different manufacturing methods and modifications of the titanium scaffolds have been studied to improve their capacity for bone engineering (10,25); for example, coating of the surface with bioactive substrates is a common strategy used to enhance bone formation. Studies have shown that coating of the titanium surface with binding proteins, including phosphoproteins and with thin hydroxylapatite, achieved enhancement of bone formation and osteoblast activity, respectively (12)(13)(14)16).…”
Section: Methodsmentioning
confidence: 99%